IMPLEMENTASI PENGINPUTAN DATA COMPONENT ELECTRONICA BERBASIS WEB MENGGUNAKAN METODE AGILE - Sihombing, Nita Anggrina; Handoko, Koko (LPPM Universitas Putera Batam, 2023)
ABSTRACT Along with the rapid development of the times, human needs that are always increasing, especially increasingly advanced technology encourages every change that is much more modern. A need that is indispensable for an organization, company, agency, and so on is like a website. Where the website becomes a necessity both in business activities but also needed in every sales promotion and helps in work within an organization or company. PT. PCI is one of the companies that develops in the field of technology, where the company still inputs work component data manually so that the data input is less accurate. With the help of artificial intelligence can provide solutions in inputting data Entering component data and providing innovation using website-based technology can provide learning for every employee to be able to increase knowledge about technology, changes in a website-based method with manual input are very different, data that was originally input manually but can be made manually automatic. AGILE is known as a form of data development, the development works collaboratively, structured and organized so that the development is able to provide ease of work. With this research carried out in order to introduce how to input data properly and correctly. Artificial intelligence used on this website that produces input component data properly and correctly for use by employees in the work process, the use of artificial intelligence is expected to be an alternative media, so that it becomes more interesting in inputting data. Keywords: PT.PCI; Artificial Intelligence; Website; Agilel; Data component